(untitled) (Sociologisk Forskning, 2022)
The present article applies Émile Durkheim’s perspective on altruism as a collective phenomenon in today’s working life. By so doing, the article re-actualizes the classic sociological problem of how altruism and working life can be reconciled. Auguste Comte and Herbert Spencer laid the foundation for two competing solutions to that question: moral regulations versus altruistic competition. Based on Durkheim’s thinking, two overlooked collective forms of altruism are elaborated: civic altruism (professional etic and civic morals) and heroic altruism (ancient virtues and military spirit). These forms of self-sacrificing altruism are relevant to the changing ideals and conditions of working life. Vertical differentiation is another factor that matters in producing altruistic heroes, such as the cosmopolitical hero, the local patriotic hero, the brave or immoral citizen in emergencies.